Analysis Effect of the Nickel Ore Reduction Process on Sulfur Fixation in Reduction Kiln #5 at PT Vale Indonesia Tbk Using Factsage Simulation - Sukamto, Untung; Furrie Mutia Rahma, Aufa Asna (Journal of Metallurgical Engineering and Processing Technology, 2024)
The pyrometallurgical process which produces a product in the form of matte nickel is a nickel product that contains high sulfur so it is necessary to carry out a calcination process with the addition of sulfur and coal in the process using a reduction kiln. In order to increase the effectiveness of the process, PT Vale Indonesia Tbk's reduction kiln operations underwent several improvisations regarding the parameters used in the reduction kiln to adapt to the ore and changes to the equipment. This research aims to obtain optimal conditions for the reduction and sulfidation process to produce nickel in a reduction kiln with low fuel consumption. This research stage was carried out by making direct observations in the field as material for assessing actual conditions, then carrying out simulations using Factage software to obtain ideal conditions. Factage simulation results show an optimal calcine composition with 1.95% Ni; 25.86% Fe; 5.03%C; 63.28% Mg2Si2O6; and 3.03% Mg2SiO4 with a good calcine temperature of 717oC and federate at a kiln reduction of 767 DMT and the maximum sulfur fixation value obtained was 1.3 because sulfur and coal were added at the ideal dose, namely 9 kg/t and 35 kg/t.